T Cells and Cancer: How Metabolism Shapes Immunity - Molon, Barbara; Calì, Bianca; Viola, Antonella (Frontiers in Immunology, 2016)
Tumour microenvironment is characterized by a consistent reduction in oxygen and blood-borne nutrients that significantly affects the metabolism of distinct cell subsets. Immune cells populating malignant lesions need to activate alternative pathways to overcome tumour-prolonged nutrient deprivation. In particular, the metabolic switch occurring in transforming tissues dramatically impacts on tumour-infiltrating T cell biology. Remarkably, the recruitment and activation of T cell within cancers are instrumental for effective anti-tumour response. Therefore, T cell metabolic adaptation acts as crucial checkpoint hijacked by tumours to dampen anti-tumour immunity.